Corrosion and degradation behavior of MCSTE-Processed AZ31 magnesium alloy - Khaled B. Abdelfattah; Marwa A. Abbas; Waleed H. El-Garaihy; Adel M. A. Mohamed; Hanadi G. Salem (Scientific Reports)
Abstract This study aims to investigate the impact of multi-channel spiral twist extrusion (MCSTE) on the corrosion and degradation properties of biodegradable AZ31 (Mg-3Al-1Zn, wt.%) magnesium alloy. Square AZ31 billets were processed using route C-MCSTE (with a 180° rotation between passes) at 250°C and with a ram speed of 10 mm/min for up to 8 passes. The extrusion process was conducted via dies with twist angles of 30° and 40°. The microstructural changes and grain size distribution in the alloy were determined with a Scanning Electron Microscopy equipped with Electron Backscatter Diffraction. Electrochemical tests were conducted in a simulated body fluid to model the environment in which medical implants operate. The mechanical properties of the alloy were tested before and after processing using compression tests. The billets processed with a 30° twist angle demonstrated superior mechanical and corrosion resistance compared to those processed with a 40° die. A 66% reduction in grain size was found in billets processed for 4 passes using the 30°-die as compared to the as-annealed condition. Billets processed for 4 and 8 passes showed ultimate compressive strength improvements of 23% and 31%, respectively compared to the as-annealed condition. The 8-pass processed sample using the 30° twist ring die showed 76% improvement in the corrosion rate compared to the as-annealed state. Furthermore, billets processed for 4 passes showed corrosion resistance and ultimate compressive strength improvements of 108% and 23%; respectively compared to the as-annealed condition. These findings imply that the developed MCSTE process can be adopted for industrial use, especially in the manufacturing of biodegradable magnesium alloys for medical implants.